2022
DOI: 10.3892/ol.2022.13226
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/YAP signaling promotes migration and invasion of DLD‑1 colorectal cancer cells

Abstract: Colorectal cancer (CRC) is one of the most prevalent malignant diseases and metastasis is the leading cause of poor prognosis in patients with CRC. Further knowledge of the molecular mechanism underlying metastasis in CRC and the identification of new therapeutic targets are needed. Yes-associated protein (YAP) is a transcriptional regulator that is important in tumorigenesis and tumor cell proliferation. The present study investigated whether YAP was crucial for CRC migration and invasion. The protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The key role played by YAP in cell migration, both in development and in cancer metastasis, has been well documented [ 1 , 38 , 48 ], but the molecular mechanisms involved in its regulation remain poorly described [ 49 ]. We therefore tested the role of ERK5 in the YAP-induced migration of HuH7 cells that display, together with an epithelial phenotype, a low rate of motility.…”
Section: Resultsmentioning
confidence: 99%
“…The key role played by YAP in cell migration, both in development and in cancer metastasis, has been well documented [ 1 , 38 , 48 ], but the molecular mechanisms involved in its regulation remain poorly described [ 49 ]. We therefore tested the role of ERK5 in the YAP-induced migration of HuH7 cells that display, together with an epithelial phenotype, a low rate of motility.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that FGFR4 signaling inhibits the activity of YAP by phosphorylating the upstream MST1/2 [ 34 ]. In addition, YAP expression was also induced by PI3K/AKT signaling, which was also repressed along with FGFR4 inhibition [ 35 , 36 ]. However, in the present study, we found that the phosphorylation of MST1/2 and LAST1/2 was only slightly changed after the addition of FGFR4 inhibitor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An effector of this pathway, mTOR, phosphorylates the Hippo pathway and favors YAP1 activity, stimulating the proliferation and invasion of glioblastoma cells ( 79 ). In colorectal cancer, the PI3K/AKT pathway activates YAP1, leading to increased invasion and migration ( 80 ).…”
Section: Key Factors In Rr and The Hippo Pathwaymentioning
confidence: 99%